2017
DOI: 10.1097/md.0000000000009044
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T gene polymorphism and the severity of coronary lesions in acute coronary syndrome

Abstract: The association between methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, circulating levels of homocysteine (Hcy), and the severity of coronary lesion in patients with acute coronary syndrome (ACS) remains unknown.Consecutive ACS patients were included. MTHFR C677T polymorphisms were determined via amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). Gensini scores were used to evaluate the severity of coronary lesions.Three hundred ten ACS patients were included, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(34 reference statements)
1
14
0
2
Order By: Relevance
“…The fact that homozygous TT for MTHFR C677T produced the enzyme with the least activity when compared with heterozygous CT and wild-type CC ,thereby leading to elevated level of serum Hcy,could be the reason for this. These results were in agreement with previous studies [21]. In one particular study, however, no significant association was found between MTHFR C677T and CAD severity [22].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The fact that homozygous TT for MTHFR C677T produced the enzyme with the least activity when compared with heterozygous CT and wild-type CC ,thereby leading to elevated level of serum Hcy,could be the reason for this. These results were in agreement with previous studies [21]. In one particular study, however, no significant association was found between MTHFR C677T and CAD severity [22].…”
Section: Discussionsupporting
confidence: 83%
“…Mutations of C677T and A1298C in the MTHFR gene result in the production of a thermolable enzyme with reduced activity.Homozygous mutations of these sites induce an approximately 70 and 40% decrease of the normal enzyme activity, respectively, which is responsible for the occurrence of hyperhomocystinemia [6]. Numerous studies have proved the relationship between MTHFR mutation and hyperhomocystinemia [21, 25, 27-29]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports have demonstrated that MTHFR C677T polymorphism is associated with other pathologies . On the other hand, there is no consensus on the effect of this polymorphism in the susceptibility to CLL .…”
Section: Descriptive Statistics Of Clinical Data and Summary Of Genotmentioning
confidence: 99%